Mínimo paramiológico brasileiro: fundamentos teórico-metodológicos - Fernandes, Sebastiana Sousa Reis (2014)
This research seeks to establish the theoretical and methodological basis for identifying key sayings of Brazilian knowledge, who can testify of the linguistic competence of a Brazilian speaker. The study aims to establish the Portuguese of paremiological Minimum of Brazil, through an experimental research that is included in the Applied Linguistics area, anchored in the field of phraseology, with support in literature. The method applied for construction of the data was the statistician, with a quantitative approach, looking at the strategies the availability and recognition of proverbs presented to informants of different ages and educational levels. To establish this minimum paremiological we start from theoretical assumptions established in similar studies in other languages such as Permiakov (19890, Russian language; Tarnosvska (2002), Spanish; Vyshnya (2008), Ukrainian language. On establishing the Brazil Portuguese paremiological the minimum, we see how many and which proverbial sentences a native speaker knows to be considered a competent user of the language in relation to the saying, considering that the proverbs are part of the cultural background of the members of a given speech community. The results achieved may contribute to the enrichment of paremiological collection of the Portuguese of Brazil, as well as serve as a teaching tool for students, teachers and maternal and foreign language translators, when available a copy in educational institutions in which they work and, later, with the publication of the same.